Status of parasitological indicators and morbidity burden of onchocerciasis after years of successive implementation of mass distribution of ivermectin in selected communities of Yeki and Asosa districts, Ethiopia - Gebremedhin Gebrezgabiher; Zeleke Mekonnen; Delenasaw Yewhalaw; Asrat Hailu (BMC, 2020)
Abstract Background Control and elimination of onchocerciasis requires regular follow-up and evaluation of community directed treatment with ivermectin (CDTi) program implementation. This research was aimed to assess the epidemiological status of onchocerciasis in disease endemic communities of Asosa and Yeki districts of Ethiopia after 5 and 15 years of successive CDTi respectively, and to evaluate the decline in infection and morbidity burden. Methods A community-based cross-sectional study was conducted from August 2017 to January 2018 (i.e. within 2-7 months since the last treatment) using interview, physical and parasitological examinations. Pre-CDTi epidemiological data were obtained from studies conducted prior to the launch of CDTi. Results A total of 3002 individuals (1567 from Asosa and 1435 from Yeki) were included. No infection was detected from Yeki. In Asosa, the prevalence of infection was 1.6%. The geometric mean intensity of infection was 0.02 mf/mg of skin snip. The prevalence rates of dermatitis, depigmentation, nodule, and atrophy in Yeki were 33(2.3%), 57(4%), 37(2.6%) and 11(0.7%), respectively. The prevalence rates of papular dermatitis, depigmentation, palpable nodule, atrophy, and blindness in Asosa were 94(6%), 38(2.4%), 30(1.9%), 28(1.8%) and 2(0.1%), respectively. Five years of CDTi had significantly reduced prevalence and intensity of infection by 91.8% (p < 0.001) and 99.7% (p < 0.001), respectively. Moreover, CDTi reduced prevalence of papular dermatitis by 95.9% (p < 0.001), palpable nodule by 90.5% (p < 0.001), and atrophy by 30% (p = 0.6) in Yeki. Similarly, CDTi reduced prevalence of papular dermatitis by 88.6% (p < 0.001), depigmentation by 90.3% (p < 0.001), atrophy by 89.5% (p < 0.001), and blindness by 90% (p < 0.001) in Asosa. Conclusions Fifteen years of successive CDTi had brought the infection from high to zero in Yeki. However, thorough entomological and serological data need to be generated to ascertain whether complete interruption of parasite transmission has been attained, and for considerations of an evidence-based CDTi cessation. Five years of CDTi in Asosa has significantly reduced the infection and morbidity of onchocerciasis to very low level. We, hereby, recommend biannual CDTi to continue in Asosa and its surroundings until the infection transmission is fully interrupted.